Research with Impact: Knowledge Mobilization Institutional Strategy 2019-2021 - Office of Vice-President Research (Université d'Ottawa | University of Ottawa, 2020)
This uOttawa knowledge mobilization strategy, identified by the working group, builds on our collective rich base of expertise and provides the support our entire research community needs to mobilize and increase the impact of their research. The strategy aims to 1) build skills; 2) promote culture; 3) engage knowledge users and 4) evaluate outcomes and generate impact.
Keywords: knowledge mobilization; strategy; higher education institutions; impact; University of Ottawa; research